Direct evidence for the interaction of stathmin along the length and the plus end of microtubules in cells. Issue 9 (9th June 2016) - Nouar, Roqiya; Breuzard, Gilles; Bastonero, Sonia; Gorokhova, Svetlana; Barbier, Pascale; Devred, François; Kovacic, Hervé; Peyrot, Vincent
ABSTRACT: Stathmin is a prominent destabilizer of microtubules (MTs). Extensive in vitro studies have strongly suggested that stathmin could act by sequestering tubulin and/or by binding to MT tips. In cells, the molecular mechanisms of stathmin binding to tubulin and/or MTs and its implications for the MT dynamics remain unexplored. By using immunofluorescence resonance energy transfer and fluorescence recovery after photobleaching, we analyzed the ability of stathmin and its phosphorylated forms (on Ser16, −25, −38, and −63) to interact with tubulin and MTs in A549 cells. Consistent with in vitro studies, we detected stathmin–tubulin interactions at the MT plus ends and in the cytosol. Of interest, we also observed a novel pool of stathmin bound along the MT. Expression of truncated stathmin and use of MT‐stabilizing taxol further showed that the C‐terminal domain of stathmin is the main contributor to this binding and that the phosphorylation state of stathmin plays a role in its binding along the MT wall. Our findings demonstrate that stathmin binds directly along the MT wall. This pool of stathmin would be readily available to participate in protofilament dissociation when the moving plus end of a depolymerizing MT reaches stathmin molecules.—Nouar, R., Breuzard, G., Bastonero, S., Gorokhova, S., Barbier, P., Devred, F., Kovacic, H., Peyrot, V. Direct evidence for the interaction of stathmin along the length and the plus end of microtubules in cells. FASEB J. 30, 3202–3215 (2016). www.fasebj.org